ENGLISH LANGUAGE LEARNING THROUGH WRITING INFOGRAPHIC - Andayani, Wuwuh; Chaeruman, Uwes Anis; Lustyantie, Ninuk (Journal of Language and Literature, 2024)
The abundance of information in text and visual formats poses challenges for learners in effectively understanding and utilizing it. This study investigated the role of infographic writing, facilitated by the Canva application, in enhancing English language learning at Institut Ilmu Sosial dan Manajemen STIAMI. Specifically, it examined how infographic creation supports the development of persuasive writing skills, drawing on Victor Schwab’s Writing Theory, which identifies five essential elements: grabbing attention, showing benefits, providing proof, convincing, and calling to action. Using a descriptive case study method, the research analyzed 82 student-created infographics from the English class in the Business Administration study program. The methodology included evaluating the infographics against Schwab’s criteria and assessing their alignment with the Semester Learning Plan (RPS) to determine whether learning outcomes matched the instructional objectives. The findings revealed that while infographic writing offers potential for enhancing visual and linguistic competencies, most infographics did not meet all five criteria of Schwab’s persuasive writing framework. Common deficiencies included weak attention-grabbing elements and insufficient proof or calls to action. Furthermore, the analysis showed misalignment between the expected learning outcomes in the RPS and the actual results, particularly in terms of text structure and linguistic precision. These gaps highlighted the need for clearer instructional guidelines and targeted teaching strategies to help students effectively integrate persuasive writing principles into infographic design. This study underscored the importance of aligning pedagogical tools like infographics with established learning goals to maximize their impact on English language acquisition.